Clinical Efficacy Of Diagnostic Laparoscopy In Abdominal Trauma (Texas Journal of Medical Science, 2026)
The article examines the clinical efficacy of diagnostic laparoscopy in abdominal trauma. Based on the analysis of 129 patients treated at the clinic of Tashkent State Medical University from 2023 to 2025, it was demonstrated that laparoscopy is the most informative minimally invasive method in cases of unclear clinical presentation. The authors developed and substantiated specific indications for this procedure, including the dynamics of pain syndrome, the presence of free fluid detected by ultrasound, and changes in hemodynamic parameters. The use of this technique allows timely identification of internal organ injuries and significantly reduces the number of unnecessary exploratory laparotomies.